METROFOOD-RI: Pilot services with physical, remote and virtual access. (December 2021) - Vandermeiren, Karine; Sharma, Subhalakshmi; Belc, Nastasia; Mast, Jan; Matuszczak, Agnes; Presser, Karl; Verleysen, Eveline; Zoani, Claudia; Van Loco, Joris
Abstract: METROFOOD-RI (www.metrofood.eu ) is an ESFRI research infrastructure, funded upon the EU H2020 METROFOOD-PP project for its Preparatory Phase, aiming to establish a new distributed European Research Infrastructure (RI) to promote scientific excellence and increase efficiency in food quality and food safety. It strives to provide and coordinate high-level metrological services on a European scale for researchers, laboratories, food inspection agencies and policymakers. As part of the preparatory phase towards the legal statute of ERIC (European Research Infrastructure Consortium), a service portfolio is being set up along with its provision diagram. As a test for this model of service provision, three use cases have been defined that are representative of the different types of access that will be provided by METROFOOD-RI: 1. physical access to a food pilot plant for demonstrating technical solutions and adaptations of food processing technology to minimize acrylamide in bakery products at the National Research & Development Institute for Food Bio-resources (IBA, Romania). 2. remote access to the transmission electron microscope facility for physicochemical characterization of nanoparticles in food (Sciensano, Belgium). 3. virtual access to two e-services for open data use, mainly addressed to researchers, laboratories, food inspection agencies and policy makers: a search engine and database for agrifood reference materials and official methods an application programming interface (API) for a risk evaluation tool The use cases will help to evaluate the usability of the single access point of the research infrastructure and to fine-tune the access procedures and interfaces with users. This will support the elaboration of the final service chart of METROFOOD-RI including all the potential physical, electronical and integrated services that the infrastructure aims to provide to its users. The paper will give an overview and first evaluation of the use case service provision and provide an overview of the potential METROFOOD-RI service portfolio.